Crime Investigation on Theft by eighting with The Modus Of Prying Automated Teller Machine (ATM) in Jurisdiction Area of Central Java - Mohamad Rofiqi; Anis Mashdurohatun (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This study aims to: 1) Review and analyze the implementation of the criminal investigations against theft by weighting with the modus of prying Automated Teller Machine (ATM) in the jurisdiction area of Central Java. 2) Assess and analyze the factors that hinder the investigation related to solve investigator in the criminal investigations against theft by weighting with the modus of prying Automated Teller Machine (ATM) in the jurisdiction area of Central Java. 3) Assess and analyze the efforts of investigators linked the criminal investigations against theft by weighting with the modus of prying Automated Teller Machine (ATM) in the jurisdiction area of Central Java? Results: 1). The process of investigations conducted by the Central Java Police in solving criminal cases of theft through Automated Teller Machine (ATM) with prying mode in accordance with the rules contained in the Criminal Procedure Code and the Law on Police No. 2 of 2002. 2). Based on the description of the Central Java Police investigators, the obstacles faced by the team of investigators of Central Java Police, among others: a. Evidence is hidden and difficult for investigators to look suspect. b. The suspect managed to flee with his colleagues by car, so investigators have to chase. c. In providing information with convoluted.3) Relatedwith efforts to overcome obstacles investigator in a criminal law enforcement ATM theft with prying mode is as follows: a. In search of evidence of the crime of investigators need to conduct more intensive searches of suspects. b. Coordinating with other entities by way of exchange of information / Data notify each DPO (List of People Searching) and when in the area to find people who sought immediately apprise and made arrests. c. Providing information (by extension agents) to the public to participate actively in supporting the work of police in the investigation of the theft through ATM.Keywords: Investigation; Crime of Theft By Weighting; Prying Automated Teller Machine (ATM).